Measures to affect the elimination behaviour of fattening pigs in a conventional housing system - Höne, Ulrike; Schrader, Lars; Hölscher, Richard; Traulsen, Imke; Krause, E. Tobias (Frontiers in Animal Science, 2024)
Pigs try to separate their lying area from the dunging area. However, due to several factors such as pen design, increasing ambient temperatures or lack of space, pigs often lie in the dunging area or defaecate in the lying area, resulting in increased pen and animal soiling. Besides poor hygienic conditions, this may also lead to increased ammonia emissions. Thus, proper changes aiming to support structuring of conventional pens may help facilitating pigs to establish and maintain functional areas, including dunging areas. In this study, we investigated the effect of measures supporting the pigs to use pre-defined functional areas. The study was done on a conventional farm in pens with fully slatted floors. Pen and animal soiling was recorded by a scoring scheme in a total of 37 pens during two fattening periods. In the first fattening period (baseline-period), the pen design remained unchanged to evaluate the status quo. In the second fattening period (treatment-period) certain changes in 16 test pens were done to structure the pen into a designated dunging and a resting area. The remaining 21 pens served as control pens. The changes included implementing of LED-Spots, partly open pen partitions, and re-arrangement of nipple drinkers and hay racks. To compare the soiling of pens, difference of pen soiling was calculated both between the baseline and the treatment period and the control and test pens. In a first step, the difference of pen soiling between the control and test pens within both fattening periods was compared. Additionally, to control for changes of pen soiling over time, the differences between the pen soiling of the control pens during the baseline period and the treatment period were compared. The same comparison was done for the test pens. In the treatment period no significant difference in the pen soiling between the control pens and test pens was found. However, over time i.e., comparing soiling of test pens and control pens between baseline and treatment period, pigs soiled designated dunging areas more in the treatment period. The pigs in both, the test and control pens were very clean during both fattening periods.